The Effect of Extraction Method on the Extract Yield in the Carotenoid Pigment Encapsulation for Halal Natural Pigment - Fajriati, Imelda; Ikhsani, Atika Yahdiyani; Monitasari, Annisa; Zamhari, Muhammad; Kartika, Betania; Subba, Jas Raj (Indonesian Journal of Halal Research, 2022)
The Soxhlet and maceration methods were used to determine the extract yield in the carotenoid pigment encapsulation for halal natural pigment production. This study aims to obtain halal natural pigment by determining the highest extract yield from the encapsulation of β-carotene in carrots. The carrot was extracted using Soxhlet and maceration method and then continued by oven drying. The n-hexane was selected because of its better volatility than ethanol and provided less solvent residue after extraction. UV-Vis spectroscopy and Thin Layer Chromatography (TLC) were used to characterize the n-hexane yield extract. Encapsulation of the pigment was investigated by adding five grams of maltodextrin to extract n-hexane weights of 0.05, 0.50, 0.75, and 1.0 grams. The maceration method yielded a much higher yield than the Soxhlet extraction method, with 2.24% (w/w) and 0.88% (w/w), respectively. The n-hexane extract absorbed a maximum wavelength of 450 nm with a retention factor (Rf) of 0.62. These values are confirmed by comparing the band's Rf values and absorption spectra with the standard's. Light absorption spectra at wavelengths 350-500 nm confirmed an intense color expression for encapsulation containing the highest pigment concentration.